Circumventing pyroptosis via hyperactivation shapes superior immune responses of human type 2 dendritic cells compared to type 3 dendritic cells - Hatscher, Lukas; Kaszubowski, Tomasz; Amon, Lukas; Dudziak, Diana; Heger, Lukas (European Journal of Immunology, 2023)
Exploiting inflammasome activation in dendritic cells (DCs) is a promising approach to fight cancer and to augment adjuvant-induced immune responses. As inflammasome formation is typically accompanied by pyroptosis, hyperactivation—defined as inflammasome activation in the absence of pyroptosis—represents a mechanism of circumventing cell death of DCs while simultaneously benefitting from inflammasome signaling. We previously demonstrated a unique specialization for inflammasome responses and hyperactivation of human cDC2 among all human DC subsets. As recent investigations revealed heterogeneity among the human cDC2 population, we aimed to analyze whether the two recently identified cDC2 subpopulations DC2 and DC3 harbor similar or different inflammasome characteristics. Here, we report that both DC2 and DC3 are inflammasome competent. We show that DC3 generally induce stronger inflammasome responses, which are associated with higher levels of cell death. Although DC2 release lower levels of inflammasome-dependent IL-1β, they induce stronger CD4+ T cell responses than DC3, which are predominantly skewed toward a TH1/TH17 phenotype. Thus, mainly DC2 seem to be able to enter a state of hyperactivation, resulting in enhanced T cell stimulatory capacity.
CRIS-Team Scopus Importer:2023-03-31
Keywords: DC2; DC3; dendritic cells; inflammasome; pyroptosis

Clec12A, CD301b, and FcγRIIB/III define the heterogeneity of murine DC2s and DC3s - Amon, Lukas; Seichter, Anna; Vurnek, Damir; Heger, Lukas; Lächele, Lukas; Tochoedo, Nounagnon Romaric; Kaszubowski, Tomasz; Hatscher, Lukas; Baranska, Anna; Tchitashvili, Giorgi; Nimmerjahn, Falk; Lehmann, Christian; et al. (Cell Reports, 2024)
Over the last decade, multiple studies have investigated the heterogeneity of murine conventional dendritic cells type 2 (cDC2s). However, their phenotypic similarity with monocytes and macrophages renders their clear identification challenging. By creating a protein atlas utilizing multiparameter flow cytometry, we show that ESAM+ cDC2s are a specialized feature of the spleen strongly differing in their proteome from other cDC2s. In contrast, all other tissues are populated by Clec12A+ cDC2s or Clec12A− cDC2s (high or low for Fcγ receptors, C-type lectin receptors, and CD11b, respectively), rendering Clec12A+ cDC2s classical sentinels. Further, expression analysis of CD301b, Clec12A, and FcγRIIB/III provides a conserved definition of cDC2 heterogeneity, including the discovery of putative FcγRIIB/III+ DC3s across tissues. Finally, our data reveal that cell identity (ontogeny) dictates the proteome that is further fine-tuned by the tissue environment on macrophages and dendritic cells (DCs), while monocytes and plasmacytoid DCs (pDCs) display subset intrinsic default settings.
CRIS-Team Scopus Importer:2024-04-12
Keywords: CD301b; CP: Immunology; DC3; dendritic cells; heterogeneity; macrophages; monocytes; mouse; myeloid cells; proteome atlas; subpopulations

Guidelines for DC preparation and flow cytometric analysis of human lymphohematopoietic tissues - Heger, Lukas; Dudziak, Diana; Amon, Lukas; Hatscher, Lukas; Kaszubowski, Tomasz; Lehmann, Christian (European Journal of Immunology, 2022)
This article is part of the Dendritic Cell Guidelines article series, which provides a collection of state-of-the-art protocols for the preparation, phenotype analysis by flow cytometry, generation, fluorescence microscopy, and functional characterization of mouse and human dendritic cells (DC) from lymphoid organs and various non-lymphoid tissues. Within this article, detailed protocols are presented that allow for the generation of single cell suspensions from human lymphohematopoietic tissues including blood, spleen, thymus, and tonsils with a focus on the subsequent analysis of DC via flow cytometry, as well as flow cytometric cell sorting of primary human DC. Further, prepared single cell suspensions as well as cell sorter-purified DC can be subjected to other applications including cellular enrichment procedures, RNA sequencing, functional assays, and many more. While all protocols were written by experienced scientists who routinely use them in their work, this article was also peer-reviewed by leading experts and approved by all co-authors, making it an essential resource for basic and clinical DC immunologists.
CRIS-Team WoS Importer:2023-01-13

Guidelines for mouse and human DC functional assays - Clausen, Bjoern E.; Amon, Lukas; Backer, Ronald A.; Berod, Luciana; Bopp, Tobias; Brand, Anna; Burgdorf, Sven; Chen, Luxia; Da, Meihong; Distler, Ute; Dress, Regine J.; Dudziak, Diana; et al. (European Journal of Immunology, 2022)
This article is part of the Dendritic Cell Guidelines article series, which provides a collection of state-of-the-art protocols for the preparation, phenotype analysis by flow cytometry, generation, fluorescence microscopy, and functional characterization of mouse and human dendritic cells (DC) from lymphoid organs and various non-lymphoid tissues. Recent studies have provided evidence for an increasing number of phenotypically distinct conventional DC (cDC) subsets that on one hand exhibit a certain functional plasticity, but on the other hand are characterized by their tissue- and context-dependent functional specialization. Here, we describe a selection of assays for the functional characterization of mouse and human cDC. The first two protocols illustrate analysis of cDC endocytosis and metabolism, followed by guidelines for transcriptomic and proteomic characterization of cDC populations. Then, a larger group of assays describes the characterization of cDC migration in vitro, ex vivo, and in vivo. The final guidelines measure cDC inflammasome and antigen (cross)-presentation activity. While all protocols were written by experienced scientists who routinely use them in their work, this article was also peer-reviewed by leading experts and approved by all co-authors, making it an essential resource for basic and clinical DC immunologists.<br

Impact of the digital health application ViViRA on spinal mobility, physical function, quality of life and pain perception in spondyloarthritides patients: a randomized controlled trial - Palm von Alten Blaskowitz, Paloma Alexandra; Liphardt, Anna-Maria; Bouzas, Claudia; Coppers, Birte; Petit, Pascal; Vuillerme, Nicolas; Bundle, Vanessa; Rudolf, Sebastian; Knitza, Johannes; Raimondo, Maria Gabriella; Labinsky, Hannah; Hatscher, Lukas; et al. (Arthritis Research & Therapy, 2024)
Background: Spondyloarthritides (SpAs) are a group of common rheumatic diseases that often cause limited mobility and lower back pain. Physiotherapy is an integral part of treatment, but access to physiotherapy limits treatment success. Digital health applications (DHAs) enable home-based physiotherapy and could significantly improve access for SpAs patients. The aim is to investigate the clinical effects of the DHA ViViRA compared with those of standard physiotherapy. Methods: SpAs patients with chronic back pain were enrolled in a randomized controlled trial. The intervention group received ViViRA DHA, whereas the control group received standard physiotherapy. Pain (verbal rating scale, PAIN-Detect), quality of life (SF-36) and mobility (BASMI) were assessed at baseline and after 12 weeks as the primary outcomes. Results: Data from 59 participants (71.2% female, mean age 45.2 years) were analyzed. The intervention group showed a significant improvement in mobility (average BASMI score: baseline: 1.1 [range 0.7–1.5]; follow-up: 1.0 [range 0.5–1.4]; p = 0.05), whereas the control group showed a significant decrease in mobility (baseline: 1.5 [range 1.1–1.9]; follow-up: 1.8 [range 1.4–2.2]; p = 0.00). The intervention group demonstrated lower pain intensity (VRS pain level at week 3.5 ± 2.8) than did the control group (VRS pain level at week 4.5 ± 2) after 12 weeks. Conclusion: Our results highlight the efficacy of DHAs such as ViViRA in the treatment of lower back pain in SpAs patients. Compared with the current gold standard, physiotherapy, DHA use results in superior outcomes. However, further larger studies are needed to confirm these promising results. Trial registration: The study is registered in the German clinical trial registry (DRKS) under the following ID: DRKS00031254.
CRIS-Team Scopus Importer:2025-02-04
Keywords: DHA; Digital health application; E-Health; Mobility; Physical function; Psoriatic spondylitis; Spondyloarthritides; Spondyloarthropathy; ViViRA

Inflammasomes in dendritic cells: Friend or foe? - Hatscher, Lukas; Amon, Lukas; Heger, Lukas; Dudziak, Diana (Immunology Letters, 2021)
Inflammasomes are cytosolic multiprotein complexes that crucially contribute to host defense against pathogens but are also involved in the pathogenesis of autoinflammatory diseases. Inflammasome formation leads to activation of effector caspases (caspase-1, 4, 5, or 11), the proteolytic maturation of IL-1β and IL-18 as well as cleavage of the pore-forming protein Gasdermin D. Dendritic cells are major regulators of immune responses as they bridge innate and adaptive immunity. We here summarize the current knowledge on inflammasome expression and formation in murine bone marrow-, human monocyte-derived as well as murine and human primary dendritic cells. Further, we discuss both, the beneficial and detrimental, involvement of inflammasome activation in dendritic cells in cancer, infections, and autoimmune diseases. As inflammasome activation is typically accompanied by Gasdermin D-mediated pyroptosis, which is an inflammatory form of programmed cell death, inflammasome formation in dendritic cells seems ill-advised. Therefore, we propose that hyperactivation, which is inflammasome activation without the induction of pyroptosis, may be a general model of inflammasome activation in dendritic cells to enhance Th1, Th17 as well as cytotoxic T cell responses.
CRIS-Team Scopus Importer:2021-05-21
Keywords: Dendritic cell; Hyperactivation; Inflammasome; NLRP3; T cell response; Vaccination

Real-World-Evidence of Digital Health Applications (DiGAs) in Rheumatology: Insights from the DiGAReal Registry - Albrecht, Alexander; Taubmann, Jule; Minopoulou, Ioanna; Hatscher, Lukas; Kleinert, Stefan; Mühlensiepen, Felix; Welcker, Martin; Leipe, Jan; Schulz, Nils; Klemm, Philipp; Hueber, Axel; Schett, Georg; et al. (Rheumatology and Therapy, 2025)
Introduction: Prescribable digital health applications (DiGAs) present scalable solutions to improve patient self-management in rheumatology, however real-world evidence is scarce. Therefore, we aimed to assess the effectiveness, usage, and usability of DiGAs prescribed by rheumatologists, as well as patient satisfaction. Methods: The DiGAReal registry includes adult patients with rheumatic conditions who received a DiGA prescription. Data at baseline (T0) and the 3-month follow-up (T1) were collected through electronic questionnaires. Study outcomes included DiGA-specific outcome assessments as well as generic outcome assessments, including the Patient Global Impression of Change (PGIC), Patient Activation Measure (PAM®), and the German Telehealth Usability and Utility Short Questionnaire (TUUSQ). Changes between T0 and T1 were analyzed using descriptive statistics and paired tests. Results: A total of 191 patients were included between June 2022 and April 2023. Of these, 127 completed the 3-month follow-up, and 114 reported using the prescribed DiGA, with 66% reporting weekly use and 15% completing the full DiGA program. The most commonly prescribed DiGAs targeted pain management (53%). Symptom improvement was reported by 51% of patients using a DiGA, with significant reductions in exhaustion levels (p = 0.03). Significant DiGA-specific improvements were observed for DiGAs addressing back pain (p = 0.05) and insomnia (p = 0.006). However, no overall significant changes were detected in patient activation, health literacy, pain, overall health, or disease activity. Back pain and weight management DiGAs were the most effective, frequently used, and best-rated DiGAs, with symptom improvements reported by 50% to 82% of patients. Conclusion: The findings suggest that DiGAs can improve symptom management in rheumatic patients, especially for conditions like back pain and weight control. Further real-world evidence is needed and may support value-based digital health efforts and reimbursement frameworks.
CRIS-Team Scopus Importer:2025-02-17
Keywords: Digital health applications; Digital therapeutics; Patient self-management; Real-world evidence; Rheumatology

Select hyperactivating NLRP3 ligands enhance the TH1-and TH17-inducing potential of human type 2 conventional dendritic cells - Hatscher, Lukas; Lehmann, Christian; Purbojo, Ariawan; Onderka, Constantin; Liang, Chunguang; Hartmann, Arndt; Cesnjevar, Robert; Bruns, Heiko; Gross, Olaf; Nimmerjahn, Falk; Burmazovic, Ivana Ivanovic; Kunz, Meik; et al. (Science Signaling, 2021)
The detection of microorganisms and danger signals by pattern recognition receptors on dendritic cells (DCs) and the consequent formation of inflammasomes are pivotal for initiating protective immune responses. Although the activation of inflammasomes leading to secretion of the cytokine IL-1 is typically accompanied by pyroptosis (an inflammatory form of lytic programmed cell death), some cells can survive and exist in a state of hyperactivation. Here, we found that the conventional type 2 DC (cDC2) subset is the major human DC subset that is transcriptionally and functionally poised for inflammasome formation and response without pyroptosis. When cDC2 were stimulated with ligands that relatively weakly activated the inflammasome, the cells did not enter pyroptosis but instead secreted IL-12 family cytokines and IL-1. These cytokines induced prominent T helper type 1 (TH1) and TH17 responses that were superior to those seen in response to Toll-like receptor (TLR) stimulation alone or to stronger, classical inflammasome ligands. These findings not only define the human cDC2 subpopulation as a prime target for the treatment of inflammasome-dependent inflammatory diseases but may also inform new approaches for adjuvant and vaccine development.
CRIS-Team Scopus Importer:2021-05-14
Keywords: Dendritic cells; cDC2; CD1c; inflammasome; hyperactivation; L18-MDP; T cell differentiation

Select hyperactivating NLRP3 ligands enhance the TH1-and TH17-inducing potential of human type 2 conventional dendritic cells - Heger, Lukas; Hatscher, Lukas; Lehmann, Christian; Purbojo, Ariawan; Onderka, Constantin; Liang, C.; Hartmann, Arndt; Cesnjevar, Robert; Bruns, Heiko; Gross, O.; Nimmerjahn, Falk; Ivanovic-Burmazovic, I.; et al. (EXPERIMENTAL DERMATOLOGY, 2022)
CRIS-Team WoS Importer:2022-03-04

XCR1 expression distinguishes human conventional dendritic cell type 1 with full effector functions from their immediate precursors - Heger, Lukas; Hatscher, Lukas; Liang, Chunguang; Lehmann, Christian; Amon, Lukas; Lühr, Jennifer J.; Kaszubowski, Tomasz; Nzirorera, Rayk; Schaft, Niels; Dörrie, Jan; Irrgang, Pascal; Tenbusch, Matthias; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2023)
Dendritic cells (DCs) are major regulators of innate and adaptive immune responses. DCs can be classified into plasmacytoid DCs and conventional DCs (cDCs) type 1 and 2. Murine and human cDC1 share the mRNA expression of XCR1. Murine studies indicated a specific role of the XCR1-XCL1 axis in the induction of immune responses. Here, we describe that human cDC1 can be distinguished into XCR1- and XCR1+ cDC1 in lymphoid as well as nonlymphoid tissues. Steady-state XCR1+ cDC1 display a preactivated phenotype compared to XCR1- cDC1. Upon stimulation, XCR1+ cDC1, but not XCR1- cDC1, secreted high levels of inflammatory cytokines as well as chemokines. This was associated with enhanced activation of NK cells mediated by XCR1+ cDC1. Moreover, XCR1+ cDC1 excelled in inhibiting replication of Influenza A virus. Further, under DC differentiation conditions, XCR1- cDC1 developed into XCR1+ cDC1. After acquisition of XCR1 expression, XCR1- cDC1 secreted comparable level of inflammatory cytokines. Thus, XCR1 is a marker of terminally differentiated cDC1 that licenses the antiviral effector functions of human cDC1, while XCR1- cDC1 seem to represent a late immediate precursor of cDC1.
CRIS-Team Scopus Importer:2023-08-25
Keywords: antiviral immunity; cDC1; DC differentiation; IL-12; XCR1